Enhancing Performance of Low-Cost Sensors Using an Infant Care Usecase - Leah, Leah; Gupta, Khushi; Wagio, Perpetua (UIR PRESS, 2022)
The drive toward citizen observatories, remote monitoring and early warning systems has resulted in numerous Internet of things (IoT) innovations. However, affordability and availability of these solutions challenge their sustainability in areas where they are needed the most. While low-cost sensors address this challenge, their reliability is often questionable. In this respect, this study set out to evaluate techniques that can enhance the efficiency of low-cost sensors in a bid to identify ways of developing sustainable IoT solutions. Experiments conducted using an infant postnatal care prototype demonstrate the potential of the identified techniques. The results showed that sensor calibration, configuration, fabrication, fusion, and improvising techniques have the potential to enhance the quality of low-cost sensors. Future work in this area will scale the solution to other use cases.